"My baby should feel no wronged!": Digital fandoms and emotional capitalism in China. Issue 4 (December 2021) - Yin, Yiyi
As the digitalization of fandom and the fandomization of digital platforms have both been discussed recently, this study intends to analyze how the logic of digital fandom was formalized in fans' everyday media practices. Specifically, the study examines the new trends of digital fandoms in China from the perspective of emotional capitalism. Based on long-termed participated observation and semi-structural interviews, the study argues that the emotional engagement of digital fan practice was legitimated by the incarnation of virtual fan objects, the datafication of emotional labor, and the re-imagination of multi-social relationships.